Influence of β-diketone structure on optical properties of formed by Eu(III) adducts photostable transparent films with effective luminescence. (May 2022) - Knyazev, Andrey A.; Karyakin, Maksim E.; Krupin, Aleksandr S.; Galyametdinov, Yuriy G.
Abstract: Luminescent adducts of Eu(III) tris(β-diketonate) with 1, 10-phenanthroline were synthesized. The effect of the β-diketone structure on thermodynamic and photophysical properties of Eu(III) complexes was characterized. Sensitization of Eu(III) ion by various β-diketones was evaluated. The synthesized compounds are shown to form isotropic vitrified structures at room temperature allowing to produce optically isotropic vitrified films with light transmittance of over 90% and efficient luminescence. These photostable films were characterized as potential luminescent temperature sensors. Graphical abstract: Image 1 Highlights: Synthesis of mesogenic europium(III) β-diketonate complexes. Optically isotropic microscale vitrified films of europium(III) complexes. Mesogenic europium(III) β-diketonate complexes are promising materials for luminescent temperature sensors.